Analisis Risiko K3 Menggunakan Metode HIRADC pada Proses Produksi Pipa Stainless Steel di PT X - Jovita Amanda Salsabila; Sulistiya Nengse; Teguh Taruna Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
PT "X" is the largest steel pipe manufacturing company in Indonesia. The process that starts from the entry of semi-finished materials to the form of pipes that have been packaged certainly has a risk of danger. Thus, an organization must obtain procedures regarding hazard identification, risk assessment, and determining control commonly known as HIRADC. This study aims to analyze occupational safety and health risks using qualitative descriptive methods through a worker safety risk analysis approach. The object of the research is focused on the activities of the stainless steel pipe production process at PT "X" which includes three stages, namely the pipe formation process, the buffing process, and the packaging process. Based on the results of the analysis carried out, there are potential hazard risk sources in the Tolerable (TL) and Moderate (MD) categories. The observed activities can be identified as having 46 K3 risks. From the results of the risk assessment, 39 K3 risks with a percentage of 85% are at the Tolerable risk level (TL). A total of 7 K3 risks with a percentage of 15% are at the Moderate risk (MD) level. PT "X" control efforts include engineering 13%, administration 42%, and PPE 45%. Control recommendations are given at a moderate level and some at a tolerable level, including through painting the boundary line of workers' roads, replacing remote control cranes, conducting safety briefings, adding safety signs, providing guardrails, and replacing pipe cutting tools.